Occupational Disorders, Daily Workload, and Fitness Levels Among Fitness and Swimming Instructors - Merati, Giampiero; Bonato, Matteo; Agnello, Luca; Grevers, Dorothée; Gunga, Hanns-Christian; Mendt, Stefan; Maggioni, Martina Anna (Frontiers in Public Health, 2021)
Few data have been published on occupational disorders among sport instructors, especially regarding those who are expected to continuously practice while teaching. As the number of sport instructors increases, new specific information about their possible injuries, daily workload, and fitness levels is needed. The aim of this study was to assess occupational disorders, cardiorespiratory fitness, and daily workload of fitness (FI) and swimming instructors (SI). An online survey addressing occupational disorders was conduct among 435 instructors (256 FI and 179 SI). In one subgroup (57 FI and 42 SI) cardiorespiratory fitness levels were evaluated using maximal oxygen consumption (V ̇O2max) as an indicator. Daily workload was assessed by monitoring heart rate and perception of exertion (using the Borg scale). Of the two groups, FI exhibited a higher 2-year prevalence of musculoskeletal injuries and SI experienced more upper respiratory tract infections. V ̇O2max ranged from 47.0 to 51.9 ml·kg-1·min-1 and was similar for both FI and SI. Regarding the daily workload, female SI had significantly higher mean heart rate and mean heart rate to maximal heart rate ratio compared to female FI, but no significant differences between male FI and SI were found. No significant differences were observed between the perceived exertion of FI and SI. Preventive strategies for the reduction of occupational disorders in FI and SI are needed.